CITRAAN DALAM KUMPULAN PUISI KALUNG DARI TEMAN KARYA AFRIZAL MALNA - Febriadi, Revista; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This study aims to describe the images in a collection of poems from Friends Necklace Afrizal Malna work. This study focused on imagery that is divided into six images are visual imagery, auditory imagery, olfactory imagery, imagery feelings, tactile imagery and motion imagery.This research is a qualitative study using descriptive comparative method. Stages of the research done by: (1) reading poetry collection Necklace from Friends (2) marks and record the images contained in each poem. (3) inventory data associated with the images. (4) classify the data. Results of this study showed that in a collection of poems from Friends Necklace are six images. Results of this study revealed that visual imagery is more widely used in the collection of poems poets of Friends Necklace Afrizal Malna work. Diction used Afrizal Malna evoke an image of human life represented objects and human activity, so the visual images that are often used Afrizal Malna to see the events in the poem.